2003
DOI: 10.1590/s0074-02762003000400005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human immunodeficiency virus-1 in the state of Ceará, Northeast, Brazil

Abstract: We analyzed, by env and gag heteroduplex mobility assay, 149 human immunodeficiency virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
(10 reference statements)
3
21
0
3
Order By: Relevance
“…Previous studies using the same methodological approach found B" subtype frequencies ranging from 30 to 57%, depending on the geographic origin of the studied population (Covas et al 1998, Morgado et al 1998a, Gadelha et al 2003. As before, no associations between B" and the different patient exposure categories were found.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Previous studies using the same methodological approach found B" subtype frequencies ranging from 30 to 57%, depending on the geographic origin of the studied population (Covas et al 1998, Morgado et al 1998a, Gadelha et al 2003. As before, no associations between B" and the different patient exposure categories were found.…”
Section: Discussionmentioning
confidence: 49%
“…Despite the fact that the state of Espírito Santo has three important harbors (Vitória, Tubarão, and Capuaba), with an intense shipping activity, which could facilitate the introduction of new HIV subtypes from other regions of the world, data presented here show that the observed subtype distribution was similar to those previously reported for other Southeastern states (Rio de Janeiro and São Paulo), with a predominance of the B subtype . Subtype B is the most prevalent subtype in the Southeastern, Northeastern and Central-Western part of Brazil (Morgado et al 1998b, Stefani et al 2000, Gadelha et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is important to monitor subtype profiles, as their distribution has local determinants, and data from one site cannot be generalized for the entire country or even for a single geographic region. HIV-1 subtype B is the most prevalent in our country, followed by subtype F1, with sporadic cases of subtypes C, D, and A (Rossini et al 2001, Gadelha et al 2003, Soares et al 2003.…”
Section: Discussionmentioning
confidence: 93%
“…Our results reflect subtypes distribution previously observed in other Brazilian regions, as subtype B was the most prevalent (96%). The remaining two samples (4%) seem to be recombinants between subtypes B and F, what has also been described in Brazil and may explain why they do not branch with the reference samples in the phylogenetic tree (Ramos et al 1999, Gadelha et al 2003, Cerqueira et al 2004. Studies are being conducted in order to analyze subtype homologies of these samples based on additional genes.…”
Section: Discussionmentioning
confidence: 94%
“…A study performed in Santos has reported the highest drug resistance rates in the country, with 37% among recent infections and 25% among chronic cases (Sucupira et al 2007). The predominant clade in Brazil is HIV-1 B, except in some areas in the south of the country, where clade C predominates (Bongertz et al 2000, Brindeiro et al 2003, Gadelha et al 2003, Cerqueira et al 2004 The use of the BED assay to estimate HIV incidence provides further insights into the understanding of HIV epidemic dynamics (Hall et al 2008). Along with a relatively well organised public health infrastructure, this epidemiological setting may represent an interesting environment to monitor the potential of clade C expansion in the epidemic and to study the impact of clades B and C on treatment and disease outcome.…”
Section: Regions Of the Hiv-1 Polymerase (N = 57) And Envelope (N =mentioning
confidence: 99%